PENGARUH ELECTRONIC WORD OF MOUTH (e-WOM) DI MEDIA SOSIAL FACEBOOK TERHADAP KEPUTUSAN PEMBELIAN - Antonio E.L. Nyoko; Anthonia Debora Dila Semuel (Journal of Management Small and Medium Enterprises (SMEs), 2021)
The development of information technology and the internet is currently developing very widely. This greatly affects the lifestyle of most humans at this time. The internet is an important part of everyday life in terms of accessing existing social media. Changes also occur in WOM (Word Of Mouth) communication. Through e-WOM communication, WOM behavior in social media, consumers can obtain information and exchange opinions about products and services. The purpose of this research is to investigate the effect of e-WOM in social media Facebook towards Purchasing Decision on Muca Cafe Kupang. The variables in this study are the independent variable; e-WOM (Intensity, Valence of Opinion, Content) and the dependent variable; Purchasing Decision. The population in this study were consumers who befriended in social media Facebook with Muca Cafe, with a sample of 100 respondents conducted by purposive sampling method. Data collection techniques in this study using the questionnaire method. The instruments were applied Validity Test, Reliability Test, Classic Assumption Test, and Hypothesis Testing using t-Test and F Test. Data analysis techniques used Descriptive Statistics, Multiple Linear Regression, and Coefficient of Determination. The result of this study indicates e-WOM through social media Facebook has a significant effect on Purchasing Decision. Thus, Muca Café should optimize its social media Facebook to attract many consumers. Keywords: Content, Electronic Word Of Mouth, Intensity, Purchasing Decisions, Valence of Opinion